Mapping human-nature archetypes to guide global biodiversity, food security, and land-use policy - Diana Sietz; Aidin Niamir; Daniel Müller; Thomas Hickler; Keiichiro Kanemoto; Daniel Dean Moran; Kirsten Thonicke (One Earth, 2025)
Reconciling biodiversity conservation, food security, and sustainable agriculture at global scale requires a clear understanding of regional social-ecological opportunities and challenges. This understanding helps untap regional contributions to better achieve global policy targets, such as those framed in the Kunming-Montreal Global Biodiversity Framework (GBF). Yet previous global syntheses of social-ecological interlinkages remain limited in thematic and spatial detail, restricting the discussion of regional contributions and targeted policy implementation. Here, we present 25 human-nature archetypes derived from clustering of global social-ecological data revealing regional opportunities and challenges for meeting global policy targets. Our results differentiate regions with large conservation opportunities from those well suited for ecological restoration or ecological intensification. They highlight the widespread need for improving governance to enhance food security and re-design agricultural systems. Overall, our analysis supports international and national decision makers in tailoring GBF targets to regional specificities in order to more effectively achieve global sustainability goals.
Keywords: 630; decision support; land system; cluster analysis; policy effectiveness; policy tailoring; policy targeting; transformation